Excessive lithium of water induced a toxic effect on kidney via oxidative damage and inflammation in carp - Jing, Hongyuan; Zhang, Qirui; Gao, Xue-jiao (Aquaculture, 2021)
Lithium (Li) is ingested by the animal body and will be distributed throughout the body fluid environment. The model of carp with lithium exposing was established to study the effects of Li on oxidative damage and inflammatory response to kidneys. The histological analysis showed that the kidney inherent structure of the Li poisoning group was destroyed and the inflammatory cells were infiltrated. The blood analysis showed that Li content in the poisoning group was higher and the ROS level in the kidney tissue significantly increased; Li significantly inhibited the expression of GSK-3β and TSC2 in the kidney but increased the expression of TOR at the mRNA level. Under Li stimulation, MDA level increased, SOD/CAT/GSH-Px activities decreased; pro-inflammatory factors significantly increased in the poisoning group. The expression of IL-10 significantly decreased in the poisoning group compared with the control group. The expression of each protein was consistent with the mRNA level. Li inhibits the antioxidant level and enhances oxidative damage. qPCR analysis shows that the significant expression of anti-inflammatory factors was significantly inhibited, and over-expression of pro-inflammatory factors stimulated inflammatory response. Besides, Li aggravated the phosphorylation of p38, ERK, and JNK in a dose-dependent manner. All the results confirmed that excess Li causes oxidative damage to promote the occurrence of inflammatory reactions in the carp kidney. [Display omitted] •Li regulated the activity of antioxidant enzyme via GSK-3β/TSC2/TOR signal, inducing oxidative damage.•Li poisoning caused oxidative damage to activate the inflammatory response.•Li activated MAPKs signaling pathway to regulate inflammation.